ANALISIS RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO PROFITABILITAS GUNA MENGUKUR KINERJA KEUANGAN PT. KRAKATAU STEEL (PERSERO) TBK TAHUN 2019-2021 - Rensa Yuanita; Sri Suartini; Hari Sulistyo; Nanu Hasanuh (Universitas Boyolali, 2022)
This research aims to be able to find out the financial performance of one of the state-owned enterprises (SOEs) which has recently become a hot topic of public discussion because it has managed to pay its debts even though it has suffered losses for many years, namely PT Krakatau Steel (Persero) Tbk. The analysis media used is the ratio of liquidity, solvency and profitability. The data sources used in this observation are financial position statements (balance sheets) and profit and loss statements of PT. PT. Krakatau Steel (Persero) Tbk from 2019-2021 obtained from IDX (Indonesia Stock Exchange). Based on the results of this study liquidity levels, Current Ratio and Quick Rastio showed fluctuation conditions while Cash Ratio showed an increase every year. The solvency level, Debt to Assets Ratio indicates solvable conditions, while Debt to Equity Ratio describes an insolvable state. And the degree of profitability, Gross Profit Margin is afluctuation of Net Profit Margin shows an increase every year,. Return On Assets shows an increase every year and Return On Equity shows an increase every year.